Combined endobronchial and oesophageal endosonography for the diagnosis and staging of lung cancer - Vilmann, Peter; Herth, Felix (The European respiratory journal, 2015)
Tweetable abstract ERSpublications - click to tweetNew guidelines for combined endobronchial and oesophageal mediastinal nodal staging of lung cancer http://ow.ly/MwM4H